Negotiating and Contesting Identities in Linguistic Landscapes - Blackwood, Robert J.; Lanza, Elizabeth; Woldemariam, Hirut (London ; Bloomsbury Academic, 2016)
'This collection represents contemporary perspectives on important aspects of research into the language in the public space, known as the Linguistic Landscape (LL), with the focus on the negotiation and contestation of identities. From four continents, and examining vital issues across North America, Africa, Europe and Asia, scholars with notable experience in LL research are drawn together in this, the latest collection to be produced by core researchers in this field. Building on the growing published body of research into LL work, the fifteen data chapters test, challenge and advance this sub-field of sociolinguistics through their close examination of languages as they appear on the walls and in the public spaces of sites from South Korea to South Africa, from Italy to Israel, from Addis Ababa to Zanzibar. The geographic coverage is matched by the depth of engagement with developments in this burgeoning field of scholarship. As such, this volume is an up-to-date collection of research chapters, each of which addresses pertinent and important issues within their respective geographic spaces'--
Includes bibliographical references and index.
Keywords: Multilingualism -- Political aspects; Identity (Psychology) -- Language; Languages in contact; Immigrants -- Language -- Political aspects; Linguistic minorities -- Political aspects; Sociolinguistics